A study on the acceptance of i-Muamalat among BMMB customers in Kota Kinabalu / Dg Rohayati Ag Mohd Shah - Ag Mohd Shah, Dg Rohayati (2014)
Technological developments in the area of telecommunications and information technology are revolutionizing the way business is done especially in banking industry. In line with global trends, Malaysia banking industry has been undergoing tremendous changes since achieving independence in 1957. Gradual deregulation of the financial sector was commenced in the 1970's was the first step in the evolutionary process. In the 1980's Automated Teller Machines (ATM's) was introduced and can be considered as the first and most visible piece of evidence of the emerging electronic banking in Malaysia. The next step in this evolutionary process is internet banking. Internet banking has experienced massive growth in many countries and has transformed the traditional banking practice to a more convenient ways. Banks are offering more and more tools, information, and access to financial accounts to help customers achieve their financial goals. Internet banking is the easiest way to carry out banking transactions over the internet. Financial institutions that offered internet banking to their customers will lower their operating costs and reduce the number of service staff. Banking institutions that offering Islamic financial services constitute a significant and growing share of the financial system in many of countries (Kahf, M., 2003). The difference between Islamic and conventional banking system is much more related to its product and service offering that based on a commodity and using the tool in the conscience of religion values (Ahmed and Ismail, 2011).